Mathematical method for analysis of the refractive outcome after toric intraocular lens implantation - Jin, Haiying; Ou, Zhongmin; Guo, Haike; Auffarth, Gerd U.; Zhao, Peiquan (Ophthalmic research, 2016)
Purpose: We aimed to develop a self-designed software programmed with a mathematical method that analyzes the refractive outcome after toric intraocular lens (IOL) implantation, taking the axis misalignment of the toric IOL into consideration. Methods: A mathematical method that can analyze the refractive outcome after toric IOL implantation was devised. Compared with the conventional method, which performs the analysis based on precise alignment of the IOL, optional meridian orientations of the toric IOL were taken into account in this method. Self-designed computer software was developed using the mathematical method. Results: Relatively high accordance was achieved between the mathematical analysis and the actual postoperative outcome. The mean predicted spherical power was 0.37 ± 0.74 dpt, and the mean measured spherical power was 0.37 ± 0.71 dpt (paired t test, p = 0.98). The mean predicted cylindrical power was -1.35 ± 0.86 dpt, and the mean measured cylindrical power was -1.42 ± 0.85 dpt (p = 0.27). The mean predicted change in the astigmatic axis was 33.7 ± 11.8°, and the mean measured parameter was 32.5 ± 15.4° (p = 0.49). Conclusions: The advantage of the present mathematical method is that the postoperative refractive outcome can be analyzed under IOL misalignment.
Gesehen am 06.05.2020